Log tax to save the forest - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Papua New Guinea s Prime Minister has announced the reinstatement of log export taxes to 1998 levels. Environmental nongovernmental organisations have been vocal in their opposition to last year s decision to reduce log taxes. The tax reductions...